Fluted hafted bifaces in the Northeast and Clovis: A North America wide perspective using image analysis. (April 2018) - Williams, Justin P.
Abstract: The degree of variability present in fluted hafted biface morphology across North America is often debated. In this work I use a series of ratio scale linear measurements to examine variability in Early Paleoindian period fluted hafted bifaces from seven different Culture Areas across North America. Instead of analysing the actual artifacts, measurements are taken on high resolution images of the hafted bifaces. I find that the Early Paleoindian period fluted hafted bifaces from the Northeast are significantly different from those found elsewhere in terms of base depth and flute length. These differences have wide reaching implications for large scale studies of Early Paleoindian hafted bifaces. Highlights: Examines a large sample of fluted hafted bifaces from across North America Uses digital image artifact analysis Discovers key morphological differences in the fluted hafted bifaces from the Northeast